2017
DOI: 10.1080/21691401.2017.1375939
|View full text |Cite
|
Sign up to set email alerts
|

Covalent immobilization of oxylipin biosynthetic enzymes on nanoporous rice husk silica for production of cis(+)-12-oxophytodienoic acid

Abstract: Soybean lipoxygenase, recombinant rice allene oxide synthase-1 and rice allene oxide cyclase were covalently immobilized on nanoporous rice husk silica using two types of linkers: glutardialdehyde and polyethylene glycol. The immobilization efficiency achieved using glutardialdehyde-linked rice husk silica was higher than that achieved using polyethylene glycol-linked rice husk silica (50-92% and 25-50%, respectively). Immobilization on both types of matrices significantly decreased the specific activities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…For research purpose, there is permanent demand for OPDA. Now, OPDA can be synthesized by covalently immobilized recombinant rice AOS-1, together with bound soybean LOX and rice AOC, which are able to form OPDA from α–LeA up to more than 80% yield [ 82 ] or by enzymatic multi-step one-pot synthesis using all three enzymes from A. thaliana and α–LeA as substrate [ 83 ].…”
Section: Biosynthesis Of Jamentioning
confidence: 99%
“…For research purpose, there is permanent demand for OPDA. Now, OPDA can be synthesized by covalently immobilized recombinant rice AOS-1, together with bound soybean LOX and rice AOC, which are able to form OPDA from α–LeA up to more than 80% yield [ 82 ] or by enzymatic multi-step one-pot synthesis using all three enzymes from A. thaliana and α–LeA as substrate [ 83 ].…”
Section: Biosynthesis Of Jamentioning
confidence: 99%
“…and a long arm linker (ECH-PEG-linked RHS) were shown to be maintained during ten cycles although there were differences depending on the linker and enzyme type [13]. In this study, the RHS-adsorbed soybean LOX was reused five times and its activity showed gradual decreases according to the cycles of reuse (Figure 4).…”
Section: Nanoporous Rice Husk Silicaassupport Matrix For Adsorbing Somentioning
confidence: 71%
“…JA biosynthesis, which is involved in the production of unstable intermediates by participating enzymes located in other cellular organelles, has encountered obstacles with in vivo production and regulation. To overcome this inconvenience, enzyme immobilization can effectively mimic the multistep JA biosynthesis by co-immobilization regardless of cellular location [13].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, this would protect the 12,13-EOT intermediate, and prevent its premature dissolution, by effectively coupling catalysis in the active sites of OsAOC and OsAOS1. We previously reported a substrate channeling effect, when OsAOC and OsAOS1 were immobilized on nanoporous rice husk silica (Le et al, 2017 ). Data presented here also demonstrate a hyperbolic dependence of OsAOC reaction yield on the molar ratio of OsAOC to OsAOS1, and this is consistent with the proposed substrate channeling (Figure 7A ).…”
Section: Discussionmentioning
confidence: 99%